HR Personnels Perception for the Importance and Success of Social Networking Sites Integration in Recruitment - Ezam, Quratulain; Ahmad, Nawaz; Jalbani, Amant Ali (International Journal of Experiential Learning & Case Studies, 2018)
Today in the period of globalization when everybody and everything appears to be associated over the globe through the progressive improvement in the field of information technology. In the present-day business world, the utilization of the Internet has turned into an integrated and fundamental tool. Consistently an ever-increasing number of organizations arrive at the digital or virtual sphere by making their organization LinkedIn profile, Twitter account, as well as a Facebook page. The purposive, nonprobability sampling technique utilized for the current study. The sample of 203 Human Resource personnel selected from private and public limited companies. All of the HR personnel’s are serving in Karachi based private and public limited companies. All respondents are power users of Social Networking Sites in the recruitment process as well as the traditional recruitment process as predefined criteria of the study. The beneficial aspects are found out by this inquiry which may lead the awareness among HR personnel’s and companies as well that the most worthy sites for the recruitment practice are LinkedIn, Indeed.com, Rozee.pk, and Facebook.